2011
DOI: 10.4314/eje.v19i1.71416
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of improved technology in Ethiopia

Abstract: One of the means by which farm level productivity can be increased is through the introduction and dissemination of improved agricultural technologies to farmers. This is possible if and only if, information on the adoption and risk taking behaviour of farmers is known in advance. While some studies have attempted to assess the factors behind the adoption behaviour of farmers, they have either been limited in scope or they focused on few selected locations and/or commodities. The objective of this study is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
31
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 5 publications
11
31
2
Order By: Relevance
“…There exists a significant difference between adopters and non-adopters of wheat technology and information in terms of these demographic factors as depicted by the descriptive statistics. Male-headed households were found to be more probable in adopting improved wheat technology package fully and partially which is in line with the fact that female-headed households are endowed with less resource and are less exposed to new information and ideas according to Admassie and Ayele 2004. Besides, the descriptive statistics show that literate-headed household are more probable in adopting improved wheat technology package fully.…”
Section: Descriptive Statisticssupporting
confidence: 58%
See 1 more Smart Citation
“…There exists a significant difference between adopters and non-adopters of wheat technology and information in terms of these demographic factors as depicted by the descriptive statistics. Male-headed households were found to be more probable in adopting improved wheat technology package fully and partially which is in line with the fact that female-headed households are endowed with less resource and are less exposed to new information and ideas according to Admassie and Ayele 2004. Besides, the descriptive statistics show that literate-headed household are more probable in adopting improved wheat technology package fully.…”
Section: Descriptive Statisticssupporting
confidence: 58%
“…Besides, the descriptive statistics show that literate-headed household are more probable in adopting improved wheat technology package fully. This might be because education may make farmers more receptive to advice from an extension agent or more able to deal with technical recommendations that require a certain level of numeracy or literacy (Admassie and Ayele, 2004). On the other hand, households with relatively larger family size are less likely to adopt improved wheat technology package fully and partially which is a bit contradictory to the fact that such households, on one hand, do not face labor shortage that may be needed to manage the increased output which resulted from technology and information adoption and, on the other hand, higher family size necessitates increased productivity to feed the family.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…A household was considered an adopter if they utilized at least one type of certified wheat seed during the survey year. Other scholars [21][22][23][24] also measured adoption in this way. Using a multistage sampling approach, farmers were selected to constitute the sample for the study.…”
Section: Key Variable Measurementmentioning
confidence: 99%
“…The results of various empirical studies confirmed that adoption of a new technology offers opportunities for increasing productivity and production. Assefa and Gezahegn (2010), Solomon et al (2011) and Hassen et al (2012) found that age of household head, educational status, livestock holding, non-farm income, sex, and information access plays important In the second stage, members of each kebele were stratified into two groups based on their adoption status of high yielding wheat varieties. Then, a total of 174 farmers were randomly sampled (87 from each group) taking into account probability proportional to size of households in each kebele for both groups.…”
Section: Empirical Studies On Adoption Of Agricultural Technologiesmentioning
confidence: 99%